Factors affecting the thermal effects of lasers in lithotripsy: A literature review - Kiron Krishnaprasad; Ravi Teja Pathi; Mustafa Nazar (Asian Journal of Urology)
Objective: The use of lasers has been an important part of urology in the treatment of stone and prostate disease. The thermal effects of lasers in lithotripsy have been a subject of debate over the years. The objective of this review was to assess the current state of knowledge available on the thermal effects of lasers in lithotripsy, as well as explore any new areas where studies are needed. Methods: In August 2022, a keyword search on Google Scholar, PubMed, and Scopus for all papers containing the phrases “thermal effects” AND “laser” AND “lithotripsy” AND “urology” was done followed by citation jumping to other studies pertaining to the topic and 35 relevant papers were included in our study. The data from relevant papers were segregated into five groups according to the factor studied and type of study, and tables were created for a comparison of data. Results: Temperature above the threshold of 43 °C was reached only when the power was >40 W and when there was adequate irrigation (at least 15–30 mL/min). Shorter lasing time divided by lithotripsy time or operator duty cycles less than 70% also resulted in a smaller temperature rise. Conclusion: At least eight factors modify the thermal effects of lasers, and most importantly, the use of chilled irrigation at higher perfusion rates, lower power settings of <40 W, and with a shorter operator duty cycle will help to prevent thermal injuries from occurring. Stones impacted in the ureter or pelvi-ureteric junction further increase the probability of thermal injuries during laser firing.